PERSEPSI PESERTA DIDIK TENTANG HASIL SOSIOMETRI - -, Noni. K - (Bimbingan dan Konseling, 2014)
This research was based on which is still the students who have the perception that there is nobenefit of sociometry . Therefore it necessary to do the research toward students perception about theresult of sociometry. The purpose of this study to determine: 1) Students perception about popularstudents. 2) Students perceptions about unpopular students. 3) Students perceptions about click. Thisresearch is about descriptive quantitative. The population of this study is class VIII.4 with 31 students.The sample is using total sampling. The are tools used for site-data a survey from. As for the analysis ofdata using the kriterium sturgess and techniques of percentage analysis. The result of this study revealedthat: 1) Students perception about popular students in the categories are very agree. 2) Studentsperception about unpopular students in the are categories agree and fairly agree. 3) Students perceptionabout click in the are categories agree.